PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING BERBANTUAN SOFTWARE GEOGEBRA TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS - Windasari; Ichsan; Hodiyanto (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2019)
The purpose of this study was determine the mathematical understanding ability of students taught using Quantum teaching learning models in the class VIII SMP Negeri 1 Sambas cartesian coordinate material. The method used in this research is the experimental method. The form of research used is quasi-experimental design with posttest-only control design. The population in this study were all class VIII students of SMP Negeri 1 Sambas. Sampling using cluster random sampling techniques so that selected class VIIIC as experimental class 1 is using quantum teaching learning model assisted by geogebra software and class VIIIA as experimental class 2 is using quantum teaching learning model without assisted by geogebra software. The result showed that student learning outcomes after being given a quantum teaching learning model assisted by geogebra software were better than student learning outcomes after being given a quantum teaching learning model without assisted by geogebra software namely the average posttest value of experimental class 1 75,83 included in the good category while the average experimental class 2 posttest value 69,48 included in the sufficient category. Test the difference in average student learning outcomes after using the quantum teaching model assisted by geogebra software and quantum teaching without assisted geogebra software it ca be concluded that there is a sigificant increase in results between the average scores in the experimental class 1 posttest and te average value in the experimental class posttest 2.